BIMBINGAN ROHANI UNTUK MENINGKATKAN MINAT DAN MOTIVASI BELAJAR SISWA DI SMK NEGERI 1 MERDEKA - Tambunan, Hardi; Sinaga, Lorinta Rupmahita; Siagian, Rebeka br; Simamora, Dinarti; Tampubolon, Samto Rediwan (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2024)
The aim of community service (PkM) is to carry out spiritual guidance to increase students' interest and motivation in studying Christianity. This PkM was implemented at the Merdeka 1 State Vocational School, Berastagi, Karo Regency, North Sumatra. The number of spiritual guidance participants was 120 people. PkM is implemented through spiritual guidance in Christian religious subjects in 12 (twelve) meetings, from 02 to 27 February 2024. The technique for implementing PkM is spiritual guidance which includes (1) singing, (2) praying (3) explaining the material, (4) applications in daily life, (5) questions and answers, (6) playing (games). A questionnaire instrument was used to obtain data about the impact of spiritual guidance on students' interest and motivation in studying Christianity. Based on descriptive analysis it can be concluded that after following spiritual guidance; (1) students' interest in learning increases with the high category, and (2) students' learning motivation increases with the high category in studying Christianity.